Impact of Management Accounting on Decision Making: A Zimbabwean Perspective - L., Nyamwanza; N, Mvundla; E., Madzivire (Journal of Accounting, Business and Finance Research, 2020)
The aim of the study was to assess the impact of management accounting practices on the decision-making process of the entity operating within the manufacturing sector using a case of Capadvise Foods and Logistics (Pvt) Ltd. The research study was based on the period from 2014 to 2017 which was majorly characterised by huge amounts of losses. Capadvise Foods experienced huge amounts of losses in spite of the existence of management accounting practices. This encouraged the researchers to seek out an in-depth insight on the impact of management accounting on decision making in light of such losses which were continually experienced. The researchers made use of questionnaires and interviews to collect qualitative and quantitative data about the opinions and attitudes of employees and management at Capadvise Foods regarding management accounting tools. The researchers found that management accounting tools contributed positively to the organisational decision making through provision, interpretation and analysis of data, enhancement in communication, relevant cost analysis and creation of budgets and forecasting. However, the researchers found that management accounting practices were compromised by technological advancement, organisational strategy, organisational factors and intensity of market competition. After analysing the results attained the researchers recommended for Capadvise Foods which include enrolling qualified management accounting staff, decision makers are allowed to make use of internal reports generated by management accountants and adoption of management accounting practices in order to allow proper and accurate decision making to take place.